2004
DOI: 10.1200/jco.2004.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Intrathecal Liposomal Cytarabine in Children With Neoplastic Meningitis

Abstract: The maximum-tolerated dose and recommended phase II dose of liposomal cytarabine in patients between the ages of 3 and 21 years is 35 mg, administered with dexamethasone (0.15 mg/kg/dose, twice a day for 5 days). A phase II trial of IT liposomal cytarabine in children with CNS leukemia in second or higher relapse is in development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 8 publications
2
70
0
8
Order By: Relevance
“…Liposomal cytarabine has been used only in the therapeutic setting both for HIV 31 and in the general population. [24][25][26][27][28][29][30] In particular, the only study of the treatment of lymphomatous meningitis in 5 patients with HIV-NHL showed a 60% CR rate. 31 There is only limited experience in the prophylactic setting in patients with aggressive lymphoma in the general population, whereas some data have been published in patients with acute lymphocytic or myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liposomal cytarabine has been used only in the therapeutic setting both for HIV 31 and in the general population. [24][25][26][27][28][29][30] In particular, the only study of the treatment of lymphomatous meningitis in 5 patients with HIV-NHL showed a 60% CR rate. 31 There is only limited experience in the prophylactic setting in patients with aggressive lymphoma in the general population, whereas some data have been published in patients with acute lymphocytic or myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal cytarabine was administered at the standard dose of 50 mg [24][25][26][27][28][29][30][31] by lumbar sac injection on Day 1 of the systemic treatment. The use of intrathecal steroids was not allowed.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Liposomal cytarabine is a sustained release liposomal formulation of cytarabine approved for IT or intraommaya treatment of recurrent lymphomatous meningitis that allows for sustained release of cytarabine with prolonged therapeutic concentration and thus prolonged drug exposure of up to 8 days in children and 14 days in adults. [2][3][4] The use of liposomal cytarabine could potentially overcome some of the barriers to post-HSCT administration of CNS prophylaxis and may provide for improved outcome results. The primary objectives of this single-institution study were to determine the safety and tolerability of liposomal cytarabine as prophylaxis prior to and following HSCT in pediatric recipients with acute leukemia and non-Hodgkin lymphoma at risk of CNS recurrence post HSCT.…”
mentioning
confidence: 99%